An Analytical Study of Selected Development Banks in India - Vasani Sureshbhai Vithalbhai (Newinera Publisher, 2021)
The economic development of any country depends on the extent to which its financial system efficiently and effectively mobilizes and allocates resources. After the Second World War, Industrialized and less developed countries have tried to bridge long-term financing needs through the creation of national development banks for finance so, the researcher wanted to know about financial parameters related to developmental banks and to study an analytical study of selected banks. The researcher has used components like Deposits, Investments, Loans and Advances, Borrowings, Fixed assets, and other assets to an analysis of performance. The researcher has selected the period of study 6(six) years which are 2014-15 to 2019-20. The researcher has used the ANOVA test for the analysis of the performance of selected Development Bank in India. The researcher has found the highest amount of deposit has been found in NABARD and SIDBI and EXIM on second and third rank respectively. The trend of deposit in SIDBI, NABARD shows a continued upward trend, but in EXIM bank deposits shows decreasing level by comparing to the base year. During the period of study in 2018 trend of deposits decreased by 9.27 in EXIM bank. By applying ANOVA deposits of three selected development banks found 8.49 is calculated value and 3.68 is table value at the 5% level of significance, so, the null hypothesis is rejected it means there is a significant difference in the Deposits and other finding included in the research paper.